2017
DOI: 10.4103/jmp.jmp_132_16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and performance of arccheck and film using gamma criteria in pre-treatment quality assurance of stereotactic ablative radiotherapy

Abstract: Aim:The aim of this study is to assess the use of ArcCHECK (AC) as an alternative method to replace film dosimetry for pre-treatment quality assurance (QA) of three-dimensional conformal radiation therapy, intensity-modulated radiation therapy (IMRT), and volumetric-modulated arc therapy (VMAT) stereotactic ablative radiotherapy (SABR) treatment plans.Materials and Methods:Twenty-five patients with a varied diagnosis of lung, spine, sacrum, sternum, ribs, scapula, and femur undergoing SABR were selected for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“…As for the gamma passing rates analysis, the average was 99.64% in the 3%/3 mm standard of general IMRT criteria, while the even more stringent 2%/2 mm criteria also had a value of 97.08% [16,17]. These results were superior to those obtained by previous studies, which found 98%±1% and >95% based on 3%/3 mm criteria [8,9].…”
Section: Discussioncontrasting
confidence: 57%
“…As for the gamma passing rates analysis, the average was 99.64% in the 3%/3 mm standard of general IMRT criteria, while the even more stringent 2%/2 mm criteria also had a value of 97.08% [16,17]. These results were superior to those obtained by previous studies, which found 98%±1% and >95% based on 3%/3 mm criteria [8,9].…”
Section: Discussioncontrasting
confidence: 57%
“…However, a number of research publications showed how detector density can affect the GPR results. [27][28][29] Common in these publications is that it was expected that GPR would be greater by increasing detector density. It is of note, however, that increasing detector density of ArcCHECK by a factor of 2 achieves a similar detector density to the MapCHECK2.…”
Section: Sd Versus Hd Modementioning
confidence: 99%
“…The dose at isocenter was measured by placing a calibrated ion chamber (PTW N30013) in the center of the ArcCHECK phantom. Although the ArcCHECK consists of small diode detectors (0.019 mm 3 ), their spacing may not provide a high enough resolution to be used for very small fields …”
Section: Methodsmentioning
confidence: 99%